STED microscopy of living cells - New frontiers in membrane and neurobiology - Eggeling, C; Willig, K; Barrantes, F (2013)
Recent developments in fluorescence far-field microscopy such as STED microscopy have accomplished observation of the living cell with a spatial resolution far below the diffraction limit. Here, we briefly review the current approaches to super-resolution optical microscopy and present the implementation of STED microscopy for novel insights into live cell mechanisms, with a focus on neurobiology and plasma membrane dynamics. © 2013 International Society for Neurochemistry.